2002
DOI: 10.1590/s0103-90162002000300026
|View full text |Cite
|
Sign up to set email alerts
|

Development and silk production by silkworm larvae after topical application of methoprene

Abstract: Juvenile hormone analogues have been tested as insect growth regulators in silkworm (Bombyx mori), seeking an increment of silk production. These chemical products, when applied in small or moderate rates, promote the extension of the last larval instar. To understand the physiologic consequences on silk production by the silkworm strain C115 x N108, the application of methoprene, a juvenile hormone analogue, was performed to evaluate its effects on larval development and silk production. Methoprene was topica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 6 publications
1
7
2
2
Order By: Relevance
“…Essas lagartas, depois de anestesiadas, foram dissecadas em placa apropriada, utilizando-se uma solução salina (8 g de NaCl; 0,4 g de KCl e 0,2 g de CaCl 2 /1.000 mL de solução) em todo o processo, para evitar o ressecamento ou a hidratação do material, segundo técnica utilizada por TaKahaShi (1984). Depois de retiradas, as glândulas foram pesadas em balança eletrônica (Miranda et al, 2002a).…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Essas lagartas, depois de anestesiadas, foram dissecadas em placa apropriada, utilizando-se uma solução salina (8 g de NaCl; 0,4 g de KCl e 0,2 g de CaCl 2 /1.000 mL de solução) em todo o processo, para evitar o ressecamento ou a hidratação do material, segundo técnica utilizada por TaKahaShi (1984). Depois de retiradas, as glândulas foram pesadas em balança eletrônica (Miranda et al, 2002a).…”
Section: Methodsunclassified
“…Pesquisas desenvolvidas para avaliar as influências das aplicações de produtos análogos do hormônio juvenil sobre a fisiologia do bicho-daseda têm indicado que a aplicação destes produtos no quinto instar larval dos insetos aumenta a duração do período de alimentação (Kajiura et al, 1987;KaMiMura, 1995;CappEllozza et al, 1997;Miranda et al, 2002a;gangwar, 2009), o ganho de peso corporal, o peso de casulos e o teor de seda (Chowdhary et al, 1986;ahMad et al, 2007). Doses adequadas de análogos do hormônio juvenil (AHJ) induzem a maior produção de fibroína (KoTiKal;dEvaiah, 1986;Sarangi, 1988), componente principal do fio de seda (waTanabE et al, 2000).…”
Section: Introductionunclassified
“…Changamma et al (2000) observed increment of fecundity, weight of testis and ovaries after treatment of 5 th instar larvae of B. mori with Methoprene. Miranda et al (2002) reported that topical application of methoprene onto the fifth instar larvae of B. mori positively influenced the duration of the fifth instar and the weight gained by insects. The application of 1 µg methoprene resulted in the heaviest silk glands, cocoons, shell cocoons, pupae weights and silk production (approximately 24%).…”
Section: Discussionmentioning
confidence: 99%
“…Fenoxycarb application in the last larval instar delays, or completely inhibits, larval-pupal metamorphosis in a dose-dependent and application time-dependent manner [14]. Other juvenile hormone analogs methoprene [17] and ZR 515 [18] also show similar effects. Dedos and Fugo [15] reported that induction of dauer larvae by fenoxycarb in B. mori is related to the ecdysone secretion ability of the prothoracic glands, especially between 66 h and 72 h of the last instar.…”
Section: Introductionmentioning
confidence: 88%